The Effect of Energy Policy Risk on Renewable Energy - Sharipov, Kongratbay; Abdullayev, Ilyos; Kuziboev, Bekhzod; Makhmudov, Samariddin; Kalandarov, Feruz; Khaytboeva, Nigora; Ilkhamova, Zarnigor (International Journal of Energy Economics and Policy, 2025)
This study explores the association among renewable energy, energy policy risk, economic development, ESG (Environmental, Social, Governance) performance and institutional quality in the panel of 137 nations from 2000 to 2022. For the econometric estimations, Method of Moments Quantile Regression (MMQR) approach is employed which is robust for the heteroscedasticity. The findings reveal that energy policy risk curbs renewable energy development which is in line with the theoretical linkage. Moreover, the robustness checks conducted by dividing the sample into developed and developing economies also validate that energy policy risk leads to a decline in renewable energy transition. Regarding control variables, economic development, ESG performance and institutional quality, their effects vary depending on the sample of countries.